ANALISIS DESKRIPTIF GAYA KEPEMIMPINAN SITUASIONAL KEPALA RUANGAN PERAWATAN RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Deby Zulkarnain Rahadian Syah; Heru Kurnianto Tjahjono (Universitas Muhammadiyah Yogyakarta, 2014)
The PKU Muhammadiyah HospitalOf Yogyakarta is referred Islamic hospital type B in Special Governmental State Yogyakarta and Central Java. In spite of being referred hospital, in giving service and nursing care has not been optimal. Head of nursing section has significant role in organizing associate nurse in effort of better service. A successful head section must be a good identifier and could appreciating the spirit of curiosity. Four situational leadership style such as, instructing, consulting, participating and delegating, will be analyze to see the tendency of leadership style that be used by the head of nursing section of PKU Muhammadiyah Hospital of Yogyakarta.This research is the quantitative-descriptive research. Measurement tools of this research using questioners that being distribute to 94 respondent. The subject of this research is vocational nurse on inpatient room of the PKU Muhammdiyah Hospital of Yogyakarta.Result of this research in the way of leadership assessed by associate nurse on head nursing section in patient room shows that ibnu shina room used consulting style 72,7%, marwah 56,3% consulting, roudhoh 63,3% consulting, arafah 53,8% participating, shofa-musdalifah 71,4% consulting, zam-zam 81,8% participating, and multazam 72,2% consulting.The style of situational leadership dominantly applied by the head nurse section of PKU based on the assessment of associate nurse is consulting leadership. The style of situational leadership not applied by the head nurse section is instructing.